Rancang Bangun Aplikasi School & Campus Health Care Berbasis Mobile - Falihg, Yusuf Andriyanto; Sejati, Hajar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The significant increase in the use of gadget devices and awareness of health, especially among college and university students, has encouraged the development of the School & Campus Health Care application. This application is an E-Health service specifically designed for the health needs of students and students, implemented via a mobile platform. In this context, the application aims to provide a solution for students who may experience health conditions that require consultation with a doctor, but cannot yet access direct services. This research focuses on developing a consultation application that allows users to get drug prescriptions from doctors virtually. Thus, it is hoped that this application can facilitate the remote health consultation process and provide easier access for students who need medical care. The result of this research is the implementation of an application that allows students to consult with doctors via a mobile platform, as well as obtain necessary drug prescriptions. Through this application, it is hoped that an efficient solution will be created in providing health services that are responsive to the needs of students and pupils in the school or campus environment.